2005
DOI: 10.1309/ga19kpy3ylmkvwyu
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Unsatisfactory Conventional Pap Smears Owing to Inadequate Squamous Cellularity Defined by the Bethesda 2001 Criterion

Abstract: To determine the incidence of clinically significant lesions in long-term follow-up after a diagnosis of inadequate squamous cellularity using former and new criteria, we reviewed conventional Papanicolaou (Pap) smears (January-December 1998) for adequacy based on the Bethesda System 2001 criterion. Of 23,302 Pap smears evaluated in our laboratory, 114 (0.489%) were classified as unsatisfactory and 245 (1.051%) as "satisfactory but limited by" based on the 10% rule. Follow-up information for 5 years was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…7 These results were similar to those mentioned by Elumir-Tanner in their review. 8 These findings challenge the notion that the Pap cytological test needs to be repeated after a period of 2-4 months, i.e.…”
Section: Introductionsupporting
confidence: 89%
“…7 These results were similar to those mentioned by Elumir-Tanner in their review. 8 These findings challenge the notion that the Pap cytological test needs to be repeated after a period of 2-4 months, i.e.…”
Section: Introductionsupporting
confidence: 89%
“…Inappropriate reporting of unsatisfactory samples as negative has been shown to be a factor in false-negative cytology preceding cancer and provides clinicians and patients with false reassurance. 21,22 A high threshold results in unacceptable unsatisfactory rates with coinciding anxiety and unnecessary costs. In this RCT criteria for cellularity were based on Bethesda 2001.…”
Section: Resultsmentioning
confidence: 99%
“…The Bethesda 2001 criteria with a minimum of 8000 to 12 000 squamous cells for CP and 5000 cells for LBC were set arbitrarily and are controversial. 21,22 Some authors favor setting the threshold for LBC at 10 000 or even more squamous cells as a minimum.…”
Section: Resultsmentioning
confidence: 99%
“…A similar conclusion was reached in a recent study in which women who had an unsatisfactory index Pap smear had a higher hazard rate for histologic CIN-2/CIN-3 or invasive squamous cell carcinoma, especially during the first 2 years of follow-up. 50 However, Adams et al 15 observed no differences in the incidence of squamous abnormalities detected on follow-up between patients who had unsatisfactory Pap smears because of inadequate squamous cellularity, as defined by the 2001 Bethesda System, and patients who had satisfactory and negative smears.…”
Section: Unsatisfactory Lb Pap Tests/alsharif Et Almentioning
confidence: 99%
“…Furthermore, the evidence that there is an increase in abnormalities in the follow-up of women with unsatisfactory conventional Pap smears also is controversial, because the 2 studies that have attempted to address that issue using traditional and 2001 Bethesda adequacy criteria, respectively, reached different conclusions. 14,15 The objective of the current study was to asses the frequency, causes, and significance of unsatisfactory SurePath PTs, as defined by the 2001 Bethesda System, in a population that was screened predominantly by LBPTs. In addition, we compared the incidence of squamous abnormalities that occurred within a 2-year follow-up period in patients who had unsatisfactory SurePath PTs with the incidence of a matched group of patients who had negative SurePath PTs that were accessioned during the same period.…”
mentioning
confidence: 99%